507. Activation of Macrophages Enhances Susceptibility to SARS-CoV-2 Antibody-Dependent Enhancement and Promotes Damage to Downstream Epithelial Cells. (31st December 2020) - DeMarco, Jennifer K; Severson, William E; DeMarco, Daniel R; Gabbard, Jon; Palmer, Kenneth E
Abstract: Background: The distinct shift in peripheral monocyte activation and infiltration of these cells into the respiratory tract observed in severe cases of COVID-19 suggests that like SARS-CoV-1, the acute respiratory distress syndrome (ARDs) observed in SARS-CoV-2 infections may result from damage to the respiratory epithelia by improperly activated macrophages (MPs). In this study, we examined the ability of non-neutralizing antibodies to sensitize MPs to killing by SARS-CoV-2, as well as the impact of these cells on downstream epithelial cells. Methods: Raw 264.7 cells were seeded into 96-well plates at a density of 1x10 4 /well and incubated overnight in the presence or absence of heat-inactivated LPS derived from either E. coli (EC) or S. enteritidis (Sal). Cells were then treated with non-neutralizing antibodies or vehicle control at the time of infection with SARS-CoV-2. Viability was assessed 48 hours post-infection by luminescence following the addition of CellTiter-Glo® (Promega). Results: While no decrease in cell viability was observed with SARS-CoV-2 alone, the presence of non-neutralizing antibodies against either the nucleocapsid or spike protein of SARS-CoV-2 decreased cell survival to 35.98% and 53.67% of the cell control, respectively (p< 0.0001 and p=0.0003). Activation of MPs with Sal-derived LPS sensitized MPs to viral killing, even in the absence of non-neutralizing antibody (20.12% viability, p< 0.0001). This was not observed in MPs activated by EC LPS. MP activation by both Sal and EC LPS further enhanced viral killing in the presence of anti-nucleocapsid, reducing cell viability to 12.21% (0.0001) and 6.46% (p< 0.0001). Finally, supernatants collected from naïve MPs subjected to ADE markedly increased the susceptibility of Vero E6 cells to SARS-CoV-2 nearly 9.8-fold (p< 0.0001). Conclusion: Here we demonstrate that naïve MPs, normally resistant to infection by SARS-CoV-2, are rendered susceptible to viral killing by activation and the presence of non-neutralizing antibodies to SARS-CoV-2. Furthermore, MPs secrete an as yet, unknown factor that enhances the susceptibility of Vero E6 to SARS-CoV-2. Taken together, these data suggest that MPs play an important role in determining the severity of SARS-CoV-2 infection. Disclosures: All Authors : No reported disclosures